Merleau-Ponty and Nishida : artistic expression as motor-perceptual faith - Loughnane, Adam, 1978- (State University of New York Press, 2019)
"In Merleau-Ponty and Nishida, Adam Loughnane initiates a dialogue between two of the twentieth century's most important phenomenologists from the Eastern and Western philosophical worlds. Loughnane guides the reader through the complexities and innovations of Nishida's and Merleau-Ponty's theories of artistic expression and their rarely explored concepts of faith. The intricacies of both philosophers' views are illuminated by analyses of artists, including Cézanne, Sesshū, Rodin, Hasegawa, and other major figures of European, Chinese, and Japanese art history, who enact a radical form of expression that Loughnane calls the practice of "motor-perceptual faith." He argues that the artist's motor-perceptual body, as poetically articulated in Nishida's and Merleau-Ponty's early works, enacts a form of faith that can be parsed in the final writings of both philosophers. The concept of faith is enlarged through its enactment by the artist, while the concept of artistic expression is broadened by casting it as a motor-perceptual conception of faith. Merleau-Ponty and Nishida is an exciting new intercultural reading of these philosophers' writings that opens up under-explored areas of their projects. It forms an important conceptual bridge between the two, while challenging distinctions between art, philosophy, and religion, and ultimately philosophy East and West"--